UMA REVISÃO SOBRE A ANÁLISE DA MOBILIDADE URBANA PELA TEORIA DA LÓGICA SOCIAL DO ESPAÇO - Brandão, Guilherme Valle Loures; Amaral, Wilian Daniel Henriques do; Almeida, Caio Augusto Rabite de; Oliveira, Ludmila Guimarães de (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This article discusses the possibility of applying the Social Logic of Space Theory, developed by Hillier and Hanson, in the urban mobility integrated analyzes. Through a literature Systematic Review, the state-of-art and the potentialities and weaknesses of the theory application in the integrated analyzes are defined. The proposition of this theory use aims to add more analytical than normative values to the space and its possible interrelationships with urban mobility analysis. As results, except for the mentioned weaknesses, it is perceived that SS Theory application is pertinent to Urban Mobility study field.